Pengenalan Permainan Tradisional Cublak-Cublak Suweng Sebagai Warisan Budaya Bangsa - Lintangkawuryan, Yulia (Jurnal Ilmiah Pariwisata, 2018)
This research discusses the introduction of the traditional game in the country. Nusantara game activities with the introduction of those aspects in which the value of culture, philosophy, history, role, application, and benefits should be part in preserving national culture and also provide for regional cultural traits. Traditional games Cublak-Cublak Suweng is a traditional game from Central Java. The history of this game, to do with the creation of the song Cublak-Cublak Suweng, derived from Walisongo, figures propagator of Islam in Java. Cublak traditional game-cubak Suweng can be used as a medium to develop the moral capabilities of early childhood. this can be seen from the meaning contained in the game Cublak-cubak Suweng that finding treasure, position, and positions do not indulgence but everything is back to a clean conscience, conscience will more easily find what wishes are looking for, do not get lost street to forget the hereafter. While the social development of children from perminan can be seen from the child benefit: interacting and socializing with friends and build sportvitas child when a turn to play, the child should receive. The results of this study identified that the game does have a big part in the archipelago nation's cultural heritage. Through the efforts of recognition given in the project, this activities carried out that the traditional games need to be introduced to the people as a cultural preservation efforts since by recognize these games and its aspects will enhance the awareness of individuals and groups about the importance of preserving the national culture in this form of traditional games.